2015
DOI: 10.1007/bf03379619
|View full text |Cite
|
Sign up to set email alerts
|

Functional Outcome in Patients With Schizophrenia: The Concept and Measurement

Abstract: Functional outcome has attracted interest from the perspective of interventions in patients with schizophrenia. It includes a wide range of abilities, from successful performance on neurocognitive tests to living independently in the community. The functional outcome is classified into three levels: neuropsychological performance, functional capacity, and functional performance. In the last decades, much effort has been directed into the development of assessment measures covering these domains of functional o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…For example, the degree of activities of ‘Visiting friends’ is well defined as ‘Never’=0 times [0 point]; Rarely = more than once in recent 3 months [1]; Sometimes = more than once in a month [2]; Often=more than once in a week [3]. A positive correlation between scores of this Japanese version of the SFS and MCCB has been reported in our preliminary study ( Sumiyoshi and Sumiyoshi, 2015 ).…”
Section: Methodsmentioning
confidence: 89%
See 1 more Smart Citation
“…For example, the degree of activities of ‘Visiting friends’ is well defined as ‘Never’=0 times [0 point]; Rarely = more than once in recent 3 months [1]; Sometimes = more than once in a month [2]; Often=more than once in a week [3]. A positive correlation between scores of this Japanese version of the SFS and MCCB has been reported in our preliminary study ( Sumiyoshi and Sumiyoshi, 2015 ).…”
Section: Methodsmentioning
confidence: 89%
“…First, it has been shown that patients and informants ratings on the SFS were highly correlated ( Dickerson et al, 1997 ). Second, the SFS ratings have been reported to be correlated with those of the SLOF, which is an informant-based objective measure ( Sumiyoshi et al, unpublished data ).…”
Section: Discussionmentioning
confidence: 99%
“… 2 6 Functional outcome is defined as a wide range of real-world functions including independent living, financial management, employment, and leisure/social activities. 7 , 8 So, social function investigated in this study is considered to be a part of functional outcome. 9 Finding contributors to functional outcome is an important issue in schizophrenia research and clinical intervention.…”
Section: Introductionmentioning
confidence: 99%
“…In this context, intermediate functional measures, or “co-primary measures,” have attracted interest as a target for therapeutic intervention (Sumiyoshi and Sumiyoshi, in press). For example, a greater sensitivity to treatment has been reported for co-primary measures compared to primary measures in a clinical trial of lurasidone and ziprasidone (Harvey et al, 2011).…”
Section: Perspectivesmentioning
confidence: 99%